Do Not Read the Latin: Latin as Satanic Signifier in Supernatural Horror Cinema. (7th January 2021) - Banner, Nicholas
Abstract: This article examines the tropological use of the Latin language to evoke the diabolical in supernatural horror cinema. When Latin is intoned in a suitably Gothic context, horror-savvy audiences have every reason to foresee the Devil and his minions arriving in short order, and are rarely disappointed. This article examines the genealogy of this trope, modelling the prolegomena to an intellectual history of cinematic Satanic Latin. The first part of the analysis traces the development of the trope through literature via the European and American Gothic traditions, the writings of the Decadents, and supernatural horror literature. The analysis then broadens to encompass Occultism, the occult, and 'occulture' more generally as important aspects of the discourse-community within which Satanic Latin functions. Finally, the scholarly concept of 're-enchantment' from the history of religions is brought to bear on the semiotic role of Satanic Latin in its performative cinematic context.